Infrared melt temperature measurement of single screw extrusion. Issue 5 (12th July 2014) - Vera‐Sorroche, J.; Kelly, A.L.; Brown, E.C.; Coates, P.D.
<x xml:space="preserve">Abstract</x> An infrared temperature sensor has been used to provide real time quantification of the thermal homogeneity of polymer extrusion. The non‐intrusive sensor was located in the barrel of a single screw extruder, positioned such that it provided a measurement of melt temperature in the channel of the metering section of the extruder screw. The rapid response of the technique enabled melt temperature within the extruder screw channel to be monitored in real time, allowing quantification of the thermal stability of the extrusion process. Two polyethylenes were used in experiments with three extruder screw geometries at a range of screw speeds. Data generated by the infrared sensor was found to be highly sensitive to thermal fluctuations relating to the melting performance of the extruder screw. Comparisons made with an intrusive thermocouple grid sensor located in the extruder die suggested that the infrared technique was able to provide a similar level of information without disturbing the process flow. This application on infrared thermometry could prove highly useful for industrial extrusion process monitoring and optimization. POLYM. ENG. SCI., 55:1059–1066, 2015. © 2014 The Authors. Polymer Engineering & Science published by Wiley Periodicals, Inc. on behalf of Society of Plastics Engineers